2017
DOI: 10.1021/acsbiomaterials.7b00169
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Long-Term Sustained Drug Delivery for Electrospun Biopolyester Nanofibrous Membranes by Introducing Cellulose Nanocrystals

Abstract: Electrospun nanofibrous membranes of poly­(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) seems not to be ideal for biomedical applications because of their hydrophobicity, and high crystallinity, as well as weak mechanical properties. It is found that hydrophilic drug such as tetracycline hydrochloride (TH) generally is located on the hydrophobic surface of electrospun PHBV nanofibrous membranes, leading to fast drug release. Therefore, we used cellulose nanocrystals (CNCs) as rigid organic nanofillers for PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 35 publications
(219 reference statements)
2
23
0
2
Order By: Relevance
“…The EDX analysis of Cl distribution confirmed that TH was distributed both on the surface and inside of the film network (Figure S3). This was consistent with the results of other reports ,…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The EDX analysis of Cl distribution confirmed that TH was distributed both on the surface and inside of the film network (Figure S3). This was consistent with the results of other reports ,…”
Section: Resultssupporting
confidence: 94%
“…Previous study reported that the films prepared by casting drug/cationic CNFs dispersion were used to release indomethacin, but the release time was too fast (10‐20 min) . The drug release properties of the cellulose nanocrystals/poly (3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) composite films prepared by electrospinning were also investigated . Tetracycline hydrochloride (TH) was used as a model drug in their work, and the composite films had long‐term sustained release property.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation efficiency (EE) is an important parameter to evaluate the feasibility of clinical application of the developed material [44]. At the theoretical concentrations of 10%, the EE values of GSE were 88 4 ± 2 1 and 86 8 ± 1 7% for PLA and PLA/PEO nanofibers, respectively.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…The PLA nanofibrous membranes released about 60% of extract content after 24 h, but when the time was prolonged to 720 h, only an additional 4% content was released ( Figure 5(a)). The initial burst release phenomenon is probably related to the drug entrapped near to the surface of the nanofibers, leading to a high initial drug delivery [44] that cannot persist for longer times. In contrast, PLA/PEO electrospun nanofibers exhibit a more sustained release pattern with a lower burst phenomenon, in which only about 20% of drug content was released over the same period of 24 h (Figure 5(b)).…”
Section: 2mentioning
confidence: 99%
“…Drug‐loaded hydrophilic nanofibrous materials were frequently used in biomedical fields, such as wound healing, tissue engineering, and so forth . However, serve burst release was frequently occurred, which was due to the large surface area of the nanofibrous mats and the quick dissolution of the water soluble drugs.…”
Section: Resultsmentioning
confidence: 98%